2023
DOI: 10.1186/s42649-023-00085-6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors affecting akinete germination and resting cell awakening of two cyanobacteria

Abstract: Globally, cyanobacteria frequently cause blooms that outcompete other species in the waterbody, affecting the diversity, decreasing water exchange rates, and promoting eutrophication that leads to excessive algal growth. Here, Dolichospermum circinale (akinetes) and Microcystic aeruginosa (resting cells), were isolated from the sediment in the Uiam Dam in the North Han River and near Ugok Bridge in the Nakdong River, respectively. The morphology, germination process and rates, and growth was evaluated in diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Very high or low pH can alter the permeability of the cell membrane, which affects ion uptake and may also lead to a loss of soluble metabolites [66,67]. On the other hand, in Kwon et al [47], Dolichospermum circinale akinetes were shown to germinate in strong alkaline conditions of pH 12, albeit weakly (<10%) (experimental condition: temperature 25 • C, light 30 µmol m −2 s −1 , CB medium, pH 5-12) (Figure 4. 7 ⃝).…”
Section: Dissolved Oxygen (Do) Salinity and Sediment Disturbance (Mix...mentioning
confidence: 99%
See 1 more Smart Citation
“…Very high or low pH can alter the permeability of the cell membrane, which affects ion uptake and may also lead to a loss of soluble metabolites [66,67]. On the other hand, in Kwon et al [47], Dolichospermum circinale akinetes were shown to germinate in strong alkaline conditions of pH 12, albeit weakly (<10%) (experimental condition: temperature 25 • C, light 30 µmol m −2 s −1 , CB medium, pH 5-12) (Figure 4. 7 ⃝).…”
Section: Dissolved Oxygen (Do) Salinity and Sediment Disturbance (Mix...mentioning
confidence: 99%
“…It is also important to understand the life cycle of cyanobacteria by comprehensively considering the formation and germination of akinete [11]. To date, many studies have collected data on the growth and bloom development of cyanobacteria [1,13,30,41], akinete formation [11,25,35,[42][43][44], and germination [11,21,30,[45][46][47], but most such information has been fragmentary. In particular, there has been little research simultaneously considering both akinete formation and germination in the context of a comprehensive life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The pulverized suspension was sequentially filtered through 100, 60, and 10 µm nylon mesh to isolate akinetes. Following the panning method [13], the filtrate was placed on a petri dish (12 cm in diameter), and from the top layer, the floating particles were isolated and mixed with filtered (0.2 µm) sterile water to a final volume of 10 mL. The final solution was stored in a dark brown glass bottle at approximately 4 • C.…”
Section: Circinale Isolation and Culturementioning
confidence: 99%
“…Analyzing ambient distribution and the abundance of akinetes requires their separation directly from the sediment, followed by their microscopic observation [10][11][12]. In the conventional method dealing with akinetes from sediment samples, cells are separated individually using micropipettes after ultra-sonication and serial size fractionation [13]. However, it is difficult to completely remove soil particles and organic materials attached to akinetes, preventing the complete separation of the akinete from the sediment.…”
Section: Introductionmentioning
confidence: 99%